Antibacterial activity of silver nanoparticles synthesized extracellularly by soil micro flora - Lekshmi, N. C. J. Packia; Kalavathy, M.; Viveka, S.; Jeeva, S.; Brindha, J. Raja (My University, 2013)
The microbes used to synthesize the silver nanoparticles were isolated from the soil and identified as E.coli, Pseudomonas sp, Aspergillus sp, Penicillium sp and Actinomycetes sp. All the isolated organisms were cultured in broth medium and used for the synthesis of silver nanoparticles extracellularly by adding 3 -10mm AgNO3. The presence of extracellular silver nanoparticles were identified by UV – visible spectrophotometer (380-420nm) and particle size investigation. Most of the microbial synthesized products are susceptible for Proteus sp. Bioactive particles from E.coli and Actinomycetes sp. were found to be best against Klebsiella sp. The active molecule from Pseudomonas sp and Penicillium sp. showed very good sensitivity pattern against Proteus sp. The molecules formed by Aspergillus sp. showed higher sensitivity against Enterobacter sp. Among the three bacterial and two fungal species, the silver nanoparticles from the fungal organisms showed the better result against pathogens.

Gümüş nanopartiküllerini sentezlemek için kullanılan mikroplar toprak ortamından izole edilmiş ve E.coli, Pseudomonas sp, Aspergillus sp, Penicillium sp and Actinomycetes sp olarak tanımlanmıştır. İzole edilen bütün organizmalar et suyu ortamında kültürlenmiş ve 3 -10mm AgNO3 eklenerek hücre dışı gümüş partiküllerin sentezi için kullanılmıştır. Hücre dışı gümüş partiküllerin varlığı, UV Vis (380-420nm)ve partikül boyut incelemesiyle belirlenmiştir. Mikrobiyal sentezlenen ürünlerin çoğu, Proteus sp.’ye duyarlıdır. E.coli and Actinomycetes sp.’den kaynaklanan biyoaktif partiküller Klebsiella sp.’ye karşı en iyi olarak bulunmuştur. Pseudomonas sp ve Penicillium sp türlerinden kaynaklanan aktif molekül Proteus sp’ye oldukça duyarlı bir durum sergilemiştir. Aspergillus sp. Tarafından oluşan moleküller Enterobacter sp.’ye karşı yüksek duyarlılık göstermiştir. Üç bakteri ve iki mantar türleri arasında mantarlardan kaynaklanan gümüş partiküller patojenlere karşı daha iyi sonuç vermiştir.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Bacteria; Fungi; Pathogens; Antimicrobial activity; Silver particles